Developing a Community-Based Organic Waste Management Model through Biofertilizer and Black Soldier Fly (Hermetia illucens) Production - Indriyanti, Dyah Rini; Widiyaningrum, Priyantini; Dewi, Pramesti; Elawati, Nunung Eni; Jelita, Orchida Puspa; Farreza, Delia Alifia; Puspita, Maria Ayu (Journal of Community Empowerment, 2025)
Household organic waste in urban settlements remains a persistent environmental challenge due to limited community-based processing systems and low levels of waste valorization. Many waste management initiatives are still activity-oriented and lack an integrated participatory circular framework that connects environmental, economic, and social dimensions. This community engagement program aimed to develop a Participatory Circular Community Model through the conversion of household organic waste into biofertilizer and Black Soldier Fly (Hermetia illucens) feed production in Plamongansari, Semarang, Indonesia. The program applied a collaborative approach involving youth organizations and women’s community groups through structured training, hands-on practice, production mentoring, and evaluation using pre- and post-assessment instruments. Organic household waste was processed into liquid and solid biofertilizer, while carbohydrate-rich residues were utilized as substrate for Black Soldier Fly larvae cultivation. The results demonstrate significant improvements in community knowledge, technical skills, and environmental awareness, accompanied by the production of economically valuable organic fertilizer and maggot feed. The developed model illustrates how participatory circular practices can reduce household waste volume while generating micro-economic opportunities. This model offers a structured framework for sustainable urban waste management and presents strong replication potential for other urban communities seeking environmentally and economically viable waste solutions.